DETERMINATION OF NICOTINE IN TOBACCO WORKER’S URINE USING LIQUID-LIQUID EXTRACTION AND GAS CHROMATOGRAPHY-MASS SPECTROMETRY (GC-MS) - Huy, Bùi Văn; Tùng, Trương Quý; Đăng Giao, Lê Vũ (Hue University Journal of Science: Natural Science, 2017)
Nicotine concentration in urine is one of the key (critical) subclinical indices to estimate the ex-posure levels, as well as to appraise thenicotine-poisoning occupational disease. The determination of nicotine has been performedusing techniques such as ultraviolet-visible spectrophotometry and solid-phase extraction with GC/MS; however, the recoveries and the repeatability were relatively low. There-fore, a liquid-liquid extraction method combined with gas-chromatography-mass-spectrometry has been developed for the determination of nicotine in the urine sample of workers of tobacco factories. Nicotine was extracted with a dichloromethane-hexane mixture (1:1 v/v) in an alkaline solution. The organic phase was evaporated under a stream of nitrogen gas until dryness, then reconstituted to 1 mL with toluene and analyzed using a GC/MS system. This has been considered as a high-reliability and high-sensitivity meth-od with the limit of detection 2.0 μg/L, from 80 % to 109 % of recovery performance of the sample, and repeatability from 4.6 % to 9.7 %. The results of this study showed that the ranges of nicotine concentration in the urine sample of smoking and non-smoking workers of the tobacco factories were 0.013 mg/L–3.324 mg/L (n = 124) and 0.006 mg/L–1.550 mg/L (n = 423), respectively.